Curious Disciplines : Mina Loy and Avant-Garde Artisthood - Hayden, Sarah (Book collections on Project MUSE., 2018)
Foregrounding Loy's critical interrogation of Futurist, Dadaist, Surrealist, and ""Degenerate"" artisthood, and exploring her poetic legacies today, Curious Disciplines reveals Loy's importance in an entirely novel way.